Design and development of high performance swa cell design for local DNA sequence alignment / Syed Abdul Mutalib Al Junid Syed Abdul Rahman - Syed Abdul Rahman, Syed Abdul Mutalib Al Junid (Institute of Graduate Studies, UiTM, 2017)
DNA sequence alignment is expected to help in revealing important information related to the human body, disease, genetic and other biological upon discovery of the sequence alignment. Moreover, there have been intensive efforts in improving the performance of the sequence alignment process via hardware-based acceleration using the Field Programmable Gate Array (FPGA). This implementation is becoming popular due to the flexibility of the acceleration design, the ability to reduce the execution cycle, parallel computational solutions, and the ability to increase the performance of alignment at the same time. The performance of the DNA sequence alignment system strongly depends on the algorithm, design architecture and accelerator performance. This study proposed three new DNA sequence alignment accelerator system cell design and architecture based on the Smith-Waterman Algorithm (SWA) named as the new Optimized SWA Linear Gap Penalty (OSL), Optimized SWA Affine Gap Penalty (OSA), and Optimized Recursive Variable Expansion SWA Linear Gap Penalty (ORSL).